Building on skills forecasts - comparing methods and applications : conference proceedings - (:unkn) unknown (Publications Office of the European Union, 2012)
This publication is based on selected papers presented at the international expert conference "Building on the skills forecast: comparing methods and applications", organised by Cedefop in February 2011. It "helps to identify the challenges and offer solutions to skills and labour-market forecasting in general and to Cedefop projections in particular; it also discusses various national approaches, methods and results and their comparisons. It provides sound evidence and suggests innovative ways of thinking about future skills needs and supply." (Hrsg., BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2 Europa; Qualifikationsforschung; Früherkennung; Qualifikationsbedarf; Qualifikationsnachfrage; Internationaler Vergleich; Europa